Rancang Bangun Sistim Optimasi Cargo Bandara - Winanto, Sujoko (I-STATEMENT, 2017)
This paper will describe the design of a system optimization cargo airport for a comprehensive study on the development of cargo airport site selection, whether the development can be optimized through the calculation of the saturation limit or another alternative such as the reallocation of existing cargo to planning. As this paper aims to get the results of the calculation of the optimization calculations use the airport cargo facilities that serve as recommendation in the development of the airport cargo